2019
DOI: 10.1542/hpeds.2018-0212
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Acute Myocarditis: Predicting Hemodynamic Compromise at Presentation to Health Care

Abstract: BACKGROUND: The clinical spectrum of pediatric acute myocarditis ranges from minimal symptoms with intact hemodynamics to rapid cardiovascular collapse and death. We sought to identify factors on initial presentation associated with subsequent hemodynamic compromise. METHODS: We performed a retrospective cohort study of patients with acute myocarditis at a freestanding pediatric hospital from 2007 to 2016. We defined 2 cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…We found that female patients were at increased risk for mortality, which was consistent with a recent report showing a higher percentage of female patients in the high-acuity group (6). Similarly, they also found high acuity at presentation in younger patients, consistent with our findings on the inverse association between age and mortality rate.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that female patients were at increased risk for mortality, which was consistent with a recent report showing a higher percentage of female patients in the high-acuity group (6). Similarly, they also found high acuity at presentation in younger patients, consistent with our findings on the inverse association between age and mortality rate.…”
Section: Discussionsupporting
confidence: 93%
“…This report is the first to use identified risk factors for such purpose. In comparison, Wolf et al, in their single-center (a free standing children's hospital) cohort of 74 children with myocarditis, attempted to predict hemodynamic compromise using variables related to initial presentation (6). Hemodynamic compromise in their definition was a complex outcome including the need for inotropic or vasoactive medications, cardiopulmonary resuscitation, ECMO, ventricular assist devices (VAD), heart transplant, or those who died.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation